The Influence of Budget Goal Clarity, Budget Participation, and Accounting Information Systems on Managerial Performance with Organizational Commitment as a Moderating Variable (A Study on the Cosmetics Industry in Java Island) - Regina Aprianti; Etty Gurendrawati; Rida Prihatni (Indonesian Journal of Business Analytics, 2025)
This study aims to analyze the effect of budget target clarity, budgeting participation, and accounting information systems on managerial performance, as well as the role of organizational commitment as a moderating variable. The study was conducted on cosmetic industry companies operating in Java Island. The research approach used is quantitative with a survey method. Data were collected through the distribution of questionnaires to managers and finance staff involved directly in the budgeting process. Data analysis was conducted using Moderated Regression Analysis (MRA). The results show that budget target clarity, budgeting participation, and accounting information systems positively affect managerial performance. In addition, organizational commitment was found to strengthen the relationship between these three independent variables and managerial performance. These findings highlight the importance of clear budget planning, active participation in the budgeting process, and the use of adequate accounting information systems to improve managerial performance, especially when supported by high organizational commitment.